Evaluating the long-term outcomes of periodontal surgery vs. non-surgical treatment in aggressive periodontitis - Vineet Nair; Nuti S Vasoya; Dhriti H Vakharia; Saloni N Mansuri; Prachi Sutariya; Greacy Dhamelia; Heli H Patel (Wolters Kluwer Medknow Publications, 2024)
Background: Aggressive periodontitis is a severe form of periodontal disease characterized by rapid tissue destruction and tooth loss. The optimal treatment approach for managing this condition remains a topic of debate. Materials and Methods: A retrospective cohort study was conducted, involving patients diagnosed with aggressive periodontitis who received either surgical or non-surgical treatment between 2010 and 2020. Clinical and radiographic data were collected at baseline and regular intervals over a 5-year follow-up period. Surgical interventions included flap surgery, guided tissue regeneration, and bone grafting, while non-surgical treatments comprised scaling and root planning with or without adjunctive antibiotics. The primary outcomes assessed included changes in probing depth, clinical attachment level, tooth loss, and patient-reported quality of life measures. Results: A total of 120 patients were included in the study, with 60 patients in each treatment group. The surgical group demonstrated significantly greater reductions in probing depth and gains in clinical attachment level compared to the non-surgical group (P < 0.05). Tooth loss was significantly lower in the surgical group over the 5 years (P < 0.01). Patient-reported outcomes also favored the surgical group, with improved oral health-related quality of life. However, the surgical group had a higher incidence of postoperative complications. Conclusion: This study suggests that periodontal surgery yields superior long-term outcomes in the management of aggressive periodontitis compared to non-surgical treatment.